Putting the Spooks Back In? The UK Secret State and the History of Computing. - Agar, Jon (Information & Culture, 2016)
The post-World War II secret state (governmental bodies that handle national security, including signals intelligence, spying, counterintelligence, and some aspects of policing, as well as the central bureaucratic mechanisms of their control) is a lacuna in the history of UK computing. This article assesses the extent to which the UK secret state was a major user of computing technologies and examines the character of its computing tasks, as well as its relationships with industry and government, more broadly.